Fukuyama Is Right about Measuring State Quality: Now What?. Issue 4 (22nd August 2014) - Holt, Jordan; Manning, Nick
<x xml:space="preserve">Abstract</x> Much has recently been written about how to best measure governance or "state quality." Should we evaluate government performance by looking at what government achieves (outputs) as Robert Rotberg and Craig Boardman recently suggested? Or should we focus on measuring state capacity and bureaucratic autonomy, as Francis Fukuyama concludes? This commentary argues in support of Fukuyama's approach by using a public administration lens to disaggregate the public sector into two domains: upstream bodies at the center of government and downstream delivery bodies that deliver, commission, or fund services under the policy direction of government. It goes further by recommending a measurement framework that focuses on identifying indicators that are behavioral and action worthy in relation to five public management systems ultimately owned and operated by the central, upstream agencies.